Suicide and life insurance : the legal and ethical implications of suicide exclusion clauses in life insurance policies - Ncube, Princess Thembelihle (University of Pretoria, 2025)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2024.